2015
DOI: 10.1515/aep-2015-0005
|View full text |Cite
|
Sign up to set email alerts
|

Soil and plants contamination with selected heavy metals in the area of a railway junction / Zanieczyszczenie gleby i roślin wybranymi metalami ciężkimi na terenie węzła kolejowego

Abstract: Heavy metal (As, Mn, Ni, Sn, Ti) concentrations were determined in soil and plant samples collected in different areas of the railway junction Iława Główna, Poland. Soil and plant samples were collected in four functional parts of the junction, i.e. the loading ramp, main track within the platform area, rolling stock cleaning bay and the railway siding. Four plant species occurring in relatively higher abundance were selected for heavy metals analysis, although in the loading ramp and platform areas only one s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 35 publications
(21 reference statements)
2
4
0
Order By: Relevance
“…Thus, the operation of railways was considered to be the main anthropogenic source of these elements in the soil. These results are supported by previous studies [40][41][42][43][44]. It can be clearly noticed that factor one had a high loading of these heavy metals.…”
Section: Results Of the Positive Matrix Factorization Modelsupporting
confidence: 90%
“…Thus, the operation of railways was considered to be the main anthropogenic source of these elements in the soil. These results are supported by previous studies [40][41][42][43][44]. It can be clearly noticed that factor one had a high loading of these heavy metals.…”
Section: Results Of the Positive Matrix Factorization Modelsupporting
confidence: 90%
“…(Samarska and Zelenko 2018a). In line with that, Staszewski et al (2015) pointed out that the levels of metals in soil near railways are higher than the corresponding values found along tra c roads and in city centres. Similar results were obtained by research in the city of Varaždin in northwestern Croatia (unpublished data), where the highest concentrations of HMs in topsoils were found in the area of the railway station.…”
Section: Anthropogenic Sources Of Soil Pollution With Sn and Sbsupporting
confidence: 66%
“…In the work of Wiłkomirski et al (2011), the highest HM metal levels were found at the siding and in the platform area. Mętrak et al (2015) found no typical pollution pro les for the differently used areas of railway, while Staszewski et al (2015) established the highest soil contamination in the platform area.…”
Section: In Uence Of Soil Propertiesmentioning
confidence: 95%
See 1 more Smart Citation
“…Further, the Colombo-Kandy railway and main road are located parallel to the Nanuoya stream and this water body is contaminated with automobile effluents runoff with rain water. Staszewski, Malawska [40], has reported that As concentration exceeds the toxic levels in soils at both sides of railways. Solutions of As used for seasoning the railway ties as chromate copper arsenate (CCA) which can be easily leaked to the soil [41].…”
Section: Hg As CD and Pb Concentration In Fledgling Feathersmentioning
confidence: 99%